Two years results of electronic brachytherapy for basal cell carcinoma - Ballester-Sánchez, Rosa (J Contemp Brachytherapy, 2017)
PURPOSE: The use of radiation therapy (RT) for non-melanoma skin cancer (NMSC) has been changing throughout the last century. Over the last decades, the use of radiotherapy has surged with the development of new techniques, applicators, and devices. In recent years, electronic brachytherapy (eBT) devices that use small x-ray sources have been introduced as alternative to radionuclide dependence. Nowadays, several devices have been incorporated, with a few series reported, and with a short follow-up, due to the recent introduction of these systems. The purpose of this work is to describe the clinical results of our series after two years follow-up with a specific eBT system. MATERIAL AND METHODS: This is a prospective single-center, non-randomized pilot study, to assess clinical results of electronic brachytherapy in basal cell carcinoma using the Esteya(®) system. In 2014, 40 patients with 60 lesions were treated. Patient follow-up on a regular basis was performed for a period of two years. RESULTS: Twenty-six patients with 44 lesions achieved two years follow-up. A complete response was documented in 95.5% of cases. Toxicity was mild (G1 or G2) in all cases, caused by erythema, erosion, or alopecia. Cosmesis was excellent in 88.6% of cases, and good in the rest. Change in pigmentation was the most frequent cosmetic alteration. CONCLUSIONS: This work is special, since the equipment’s treatment voltage was 69.5 kV, and this is the first prospective study with long term follow-up with Esteya(®). These preliminary report show excellent results with less toxicity and excellent cosmesis. While surgery has been the treatment of choice, certain patients might benefit from eBT treatment. These are elderly patients with comorbidities or undergoing anticoagulant treatment as well as those who simply refuse surgery or might have other contraindications.